1999
DOI: 10.1111/j.1751-1097.1999.tb08304.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Phototoxicity and Biodistribution Studies of Anti‐Carcinoembryonic Antigen Monoclonal Antibody‐Phthalocyanine Conjugates

Abstract: Immunophototherapy of cancer combines the specificity of a monoclonal antibody (MAb) to an overexpressed tumor marker with the phototoxic properties of a conjugated dye. Aluminum tetrasulfophthalocyanine (AlPcS4) was covalently coupled to a 35A7 MAb directed against carcinoembryonic antigen (CEA) via a five-carbon spacer chain (A1) to yield conjugates with a molar ratio ranging from 5 to 16 mol of AlPcS4 per mol of 35A7 MAb. Conjugates were labeled with radioiodine for characterization. The immunoreactivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…However, the Pc-antibody conjugates were photoinactive, most likely due to inefficient subcellular targeting. Employing similar compounds, AlPcS 4 was covalently coupled to monoclonal antibodies directed against carcinoembryonic antigen (CEA) [76]. In vivo studies using nude mice bearing human colon carcinoma xenografts (T380) demonstrated increased uptake of the antibody-Pc conjugate as compared to the free Pc.…”
Section: Phthalocyanine Deliverymentioning
confidence: 99%
“…However, the Pc-antibody conjugates were photoinactive, most likely due to inefficient subcellular targeting. Employing similar compounds, AlPcS 4 was covalently coupled to monoclonal antibodies directed against carcinoembryonic antigen (CEA) [76]. In vivo studies using nude mice bearing human colon carcinoma xenografts (T380) demonstrated increased uptake of the antibody-Pc conjugate as compared to the free Pc.…”
Section: Phthalocyanine Deliverymentioning
confidence: 99%
“…The Ad-AlPcS 4 derivatives were tested both in vitro and in vivo. The penton base-AlPcS 4 conjugated via two linkers (compound pentonIn 1999, Carcenac et al used the same methodology to link AlPcS 4 8 to MAb 35A7 for a selective photoimmunotherapy directed against carcinoembryonic antigen (CAE) [71]. A limited immunoreactivity was observed: the 35A7 MAb-Pc conjugates showed an immunoreactivity close to that of the unconjugated antibody, independently of the number of Pcs anchored on the MAb (5, 12 or 16 mol of Pc per mol of MAb).…”
Section: Adenoviruses and Adenoviral Proteinsmentioning
confidence: 98%
“…However, their production is resource intensive, and they often cause immune reactions. Nevertheless, conjugates of photosensitizers with mAbs directed against a variety of targets have been produced, including those that target receptors for signal transduction pathways, 87 oncofoetal antigens 88 and growth factor receptors. 89 Pereira et al studied a novel PS conjugated with bovine and human serum albumin (BSA and HSA, respectively) and a monoclonal antibody, anti-CD104.…”
Section: Antibody-based Targetingmentioning
confidence: 99%